Investigation of native microbial cenoses of Arabidopsis thaliana rhizosphere in artificial substrates - Adamchuk-Chala , Nadiia; Chala , Yelyzaveta (Problems of Environmental Biotechnology, 2021)
The technology of cultivating Arabidopsis plants on an artificial substrate has been worked out. On the new substrate, the full life cycle of Arabidopsis plants was obtained, and viable seeds were obtained.